PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS E-LEARNING MENGGUNAKAN MOODLECLOUD UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Widiastuti, Monalisa Tri; Partono, Partono; Riswanto, Riswanto (Universitas Muhammadiyah Metro, 2021)
Abstract: Presurvey results at SMP Negeri 2 Banjar Agung, SMP Negeri 3 Banjar Agung and SMP Negeri 1 Way Serdang, that internet media that have been used previously have disadvantages, namely that they cannot display material and examples in the form of animation and video as a whole in one website. Therefore, it is necessary to develop learning media that can complement the shortcomings in the previous media by using moodloud. Moodlecloud is an update of the moodle application that integrates with open source applications for full online conferencing, including video, audio, images and desktop sharing. This research is a development research (Research and Development) with development models ADDIE (Analysis, Design, Development, Implementation and Evaluation) and in this research using expert tests and small group tests were conducted to see the feasibility of products. The results showed that e-learning based science learning media using moodlecloud which was developed was very feasible with a percentage of product feasibility of 93,41% and able to increase student interest in learning with a n-gain value of 0,94.Keywords: media of learning, e-learning, moodlecloud, interest in learning